proved...
Step-by-step explanation:
this is too easy method to solve this problem
it was a long proof...
follow the caption and steps and you'll understand it
Answer:
£166 : £581
Hope this helps :)
Have a great day !
5INGH
Step-by-step explanation:
2 + 7 = 9
747 ÷ 9 = 83
2 : 7
( × 83 both sides )
166 : 581
Explain
Answer:
Step-by-step explanation:
midpoint theorem : (mx₂+nx₁/m+n , my₂+ny₁/m+n)
(-3, k) = ( -3*-2 + k*-5/-3+k , -3*3 + k*-4/-3+k)
(-3, k) = (6-5k/-3+k , -9-4k/-3+k)
Compare x values of both side ;
-3 = 6-5k/-3+k
-3 *( -3+k) = 6-5k
-3*-3 +k *-3 = 6-5k
9 -3k = 6- 5k
5k -3k = 6 - 9
2k = -3
k= -3/2